EFFECT OF VANCOMYCIN ON DEEP STERNAL WOUND COMPLICATIONS AFTER CARDIAC SURGERY (The Research of Medical Science Review, 2025)
Objective: To evaluate the efficacy of topical vancomycin in reducing deep sternal wound complications in patients undergoing median sternotomy for cardiac surgery.Study Design: Randomized Controlled TrialPlace and Duration of Study: Department of Cardiac Surgery, Jinnah Hospital Lahore, over a period of four months following synopsis approval from CPSP.Methodology: A total of 100 patients undergoing cardiac surgery via median sternotomy were enrolled using non-probability consecutive sampling and randomized into two groups (n=50 each). Group A received topical vancomycin applied to the sternal edges before closure, while Group B served as the control group with standard wound care. The primary outcome was the incidence of deep sternal wound complications (DSWC) within six weeks postoperatively. Secondary outcomes included duration of mechanical ventilation, length of ICU stay, and total hospital stay. Data were analyzed using SPSS version 25. Chi-square test and independent t-test were applied where appropriate, with p-value ≤ 0.05 considered statistically significant.Results: DSWC occurred in 6.7% of patients in the vancomycin group versus 26.7% in the control group (p = 0.038; OR = 0.20; 95% CI: 0.04–0.91). Mean duration of mechanical ventilation was significantly lower in Group A (5.73 ± 1.73 hours) compared to Group B (9.83 ± 2.15 hours, p < 0.001). Similarly, ICU stay (1.87 ± 0.86 days vs. 3.33 ± 1.27 days, p < 0.001) and total hospital stay (7.00 ± 1.79 days vs. 9.87 ± 2.47 days, p < 0.001) were significantly reduced in the intervention group.Conclusion: Topical vancomycin significantly reduced the incidence of deep sternal wound complications, mechanical ventilation time, and hospital stay following cardiac surgery. It offers a safe, low-cost prophylactic strategy, particularly valuable in resource-constrained healthcare settings such as Pakistan.